Fabrication of dendritic fibrous silica nanolayer on optimized water-glass-based synthetic nanosilica from rice husk ash. Issue 21 (1st November 2022) - Tran, Ngoc Minh; Nam, Yunhee; Yoo, Hyojong
Abstract: Synthetic nanosilica derived from rice husk ash (RHA) is an eco-friendly and sustainable material that can replace silica sand and fumed silica. High surface area and large pore channels are required to extend the industrial applicability of nanosilica. To overcome the current limitations of water-glass-based synthetic nanosilica prepared from RHA (denoted as WNS), a silica-based nanoarchitecture composed of a dendritic fibrous silica nanolayer (DFSL) as the outer layer and WNS as the inner part (WNS@DFSL) was constructed. The preparation of RHA and WNS was investigated and optimized to improve the surface properties of WNS@DFSL. DFSL substantially enhances the porosity, surface area, and channel size of WNS. Moreover, the obtained WNS@DFSL can be used as an efficient template for incorporating other active components such as zeolitic imidazolate framework (ZIF-8) and ZnO. The current synthetic strategy can be used to construct hierarchical porous silica-based nanoarchitectures, thereby facilitating the industrial use of eco-friendly materials. Graphical abstract: Image 1 Highlights: Quality of water-glass-based synthetic nanosilica prepared from RHA (WNS) is optimized. Dendritic fibrous silica nanolayer (DFSL) is successfully fabricated on the surface of WNS to generate WNS@DFSL. DFSL substantially enhances the porosity, surface area, and channel size of WNS.